Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1063/1.3679725
|View full text |Cite
|
Sign up to set email alerts
|

Effect of annealing on the temperature-dependent dielectric properties of LaAlO3 at terahertz frequencies

Abstract: We present THz conductivity of LaAlO3 (LAO) as a function of temperature and annealing, using terahertz time-domain spectroscopy (THz-TDS). We observed that, after annealing, spectral weight redistribution occurs, such that the real conductivity σ1(ω) changed from a featureless and almost frequency-independent spectrum, into one where peaks occur near the phonon frequencies. These phonon frequencies increase with increasing temperature. We attribute the appearance of these absorption peaks to the diffusion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…1(g)] and an absorption coefficient similar to that reported in Ref. [13]. However, rather than representing real physical absorption the anisotropy of the refractive index has resulted in a polarization rotation.…”
supporting
confidence: 67%
See 2 more Smart Citations
“…1(g)] and an absorption coefficient similar to that reported in Ref. [13]. However, rather than representing real physical absorption the anisotropy of the refractive index has resulted in a polarization rotation.…”
supporting
confidence: 67%
“…Raman scattering and Fourier-transform spectroscopy have unveiled the influence of the rhombohedral distortion on the vibrational modes of LaAlO 3 [4,10,11]. Terahertz (THz) time-domain spectroscopy (TDS) was used previously to examine the complex refractive indexñ n iκ in [001]-oriented LaAlO 3 [12,13] below the lowest frequency optical phonons. Grischkowsky and Keiding reported a refractive index n that increased monotonically from 4.9 at 0.1 THz to 5.1 at 2.0 THz, characteristic of dispersion below an optical phonon frequency, and detected no noticable birefringence [12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, ε ∞ does not just depend on the maximum investigated frequency, as the definition indicates, but also depends on the temperature. Dielectric property studies show that the absorption modes will stiffen or soften with increasing temperature [30]; such stiffening or softening effects directly affect the frequency of the absorption modes and hence the value of ε ∞ . Hence, in our analysis, at every temperature, ε ∞ is one of the fitting parameters in the fit of σ 1 (ω) and σ 2 (ω).…”
Section: Conductivity Theoretical Fitting and Discussionmentioning
confidence: 99%
“…The temperature dependence of n was also investigated in the Terahertz regime by Zou et al 31 They found that dn/dT is small (not specified) and related to oxygen vacancies and lattice vibrations. In contrast, dn/dT in the visible range reported in this work is related to electronic excitations, see Eq.…”
Section: Temperature-dependent Measurements (80-700 K)mentioning
confidence: 99%